2017
DOI: 10.2485/jhtb.26.157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Placental Extract on Cell Proliferation, Type I Collagen Production, and ALP Secretion in Human Osteosarcoma Cell Line Saos-2

Abstract: Porcine placenta extract (P-placenta) is widely applied in medicine and cosmetics. However, few studies have examined the effect of the extract on the cellular behavior of the osteoblastic cell line Saos-2. Here, we demonstrated that P-placenta enhances the proliferation, collagen type I production, and alkaline phosphatase (ALP) secretion of Saos-2 in vitro. Proliferation of Saos-2 was assessed by MTT and DNA synthesis assays. Type I collagen production and ALP secretion were evaluated using enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Nevertheless, similar results proposing the osteogenic potential of placenta extract have been reported. Elevation of collagen type I synthesis and ALP activities of osteosarcoma cell line (Saos-2) by porcine placental extract were observed by Wang et al 31 . Additionally, research on the effects of placental extract in ovariectomized (OVX) mice reported that placental extract could enhance bone formation in OVX mice and augment ALP activity in osteoblast-like cells 67 .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Nevertheless, similar results proposing the osteogenic potential of placenta extract have been reported. Elevation of collagen type I synthesis and ALP activities of osteosarcoma cell line (Saos-2) by porcine placental extract were observed by Wang et al 31 . Additionally, research on the effects of placental extract in ovariectomized (OVX) mice reported that placental extract could enhance bone formation in OVX mice and augment ALP activity in osteoblast-like cells 67 .…”
Section: Resultsmentioning
confidence: 88%
“…In addition, expression of the osteogenic genes ALP, Runx2, BMP2, OPN , and OCN is shown in Figure 6 H, and the primary and late osteogenic genes were significantly upregulated in the hASCs cultured on the G/H/hPE scaffold compared to the G/H scaffold ( ALP : 3.4-fold, Runx2 : 3.9-fold, BMP2 : 1.7-fold, OPN : 2.4-fold, and OCN : 4.8-fold at day 21). Although the placental extract (PE) has been widely used as a therapeutic treatment, the osteogenic differentiation mechanism of PE remains to be unclear 31 . Nevertheless, similar results proposing the osteogenic potential of placenta extract have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we report the synthesis and characterization of amphiphilic dextran-vinyl laurate-based polymer (Dex-L) and evaluate its efficacy as the encapsulation platform for porcine placenta hydrolysate. Porcine placenta extract has been widely reported to possess various therapeutic benefits, including enhancement of cell proliferation (Imamura et al 2017), antioxidant activity (Tang et al 2013), and immunostimulation in pigs (Lee et al 2013). However, oral application of porcine placenta hydrolysate is susceptible to protein degradation that can occur in the digestive system and will benefit from an effective encapsulation technology.…”
Section: Introductionmentioning
confidence: 99%